2018
DOI: 10.1024/0301-1526/a000672
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of penetrating arterial trauma with stent grafts

Abstract: The endovascular treatment of penetrating arterial injuries with covered stents is feasible. However, the criteria used to choose the best method must be individualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
15
0
4
Order By: Relevance
“…Previous case reports with insertion of stents in penetrating arterial injury have not reported infectious complications. 2 , 9 Our patient did not show any signs of infection during follow-up. Long-term outcomes data for the use of carotid stents in the young population are not available.…”
Section: Discussionmentioning
confidence: 50%
“…Previous case reports with insertion of stents in penetrating arterial injury have not reported infectious complications. 2 , 9 Our patient did not show any signs of infection during follow-up. Long-term outcomes data for the use of carotid stents in the young population are not available.…”
Section: Discussionmentioning
confidence: 50%
“…In a 13-year retrospective review, penetrating injuries more often resulted in proximal subclavian artery injuries when compared to middle and distal injuries [12]. Furthermore, penetrating injuries in this area are usually the result of gunshot wounds and, less likely, stab wounds [13,14]. In a 10-year retrospective review, Lin and colleagues reported that the exact mechanism of injury was associated with outcome differences with stab wounds resulting in an 80% survival rate and gunshot wounds resulting in a 63% survival rate [13].…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular approaches for penetrating arterial trauma, which are not limited to only subclavian artery injuries, include embolization and stent graft repair. Stent graft repair is often the preferred approach as it preserves blood flow [14]. The use of many different types of stents in the treatment of axillo-subclavian artery injuries have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations